2019
DOI: 10.1088/1757-899x/571/1/012090
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis a novel Schiff base and Chalcone derivatives compounds and using as flame retardant for unsaturated polyester and epoxy resins

Abstract: In this work, seven additives were used to reduced the flammability, namely:(1- (4-hydroxy-3-methoxyphenyl)-3-(2-hydroxy-5-(6-nitrobenzothiazoldiazenyl)phenyl)pr op-2-en-1-one)(Add. I),(3-(2-hydroxy-5-(6-nitrobenzothiazoldiazenyl)phenyl)-1-(4-hydroxyphenyl)prop-2-en-1-one)(Add. II),3-(2-hydroxy-5-(6-nitrobenzohiazoldiaze nyl) phenyl)-1-(4-methoxyphenyl)prop-2-en-1-one(Add. III), 2-((2-hydroxy-4-methyl phenyl)imino)methyl)-4-(6-nitrobenzothiazoldiazenyl)phenol(Add. IV),2-(6-methyl pyridin-2-yl)imino)methyl)-4-(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…), 721. NMR spectra of 3c were published in the literature [ 1 ]. FTIR of 3d ( Figure S4 ) showed the characteristic bands at 3112 (C–H str.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…), 721. NMR spectra of 3c were published in the literature [ 1 ]. FTIR of 3d ( Figure S4 ) showed the characteristic bands at 3112 (C–H str.…”
Section: Resultsmentioning
confidence: 99%
“…), 849 (C–N str., Ar–NO 2 ). NMR spectra of 3d were published in the literature [ 1 ]. FTIR of 4a showed the characteristic bands for O–H at 3444 cm −1 , olefinic C–H at 2881 cm −1 , aromatic C–H at 2834 cm −1 , C=O at 1680 cm −1 , olefinic C=C at 1650 cm −1 , aromatic C=C at 1600,1527 cm −1 , and C–O at 1225 cm −1 [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chalcones possess α,β-unsaturated ketones, which can undergo electron-transfer reactions, making them suitable for preparing phosphorus-containing polymers . Additionally, polymers of chalcone derivatives are widely used in printing materials, photocurable coatings, and the biomedical field and as flame-retardant materials. Mani and Kathavarayan synthesized chalcone-based polyacrylamides and investigated their photo-cross-linking and flame-resistant properties . They reported that the presence of nitrogen and chalcone in the polymer backbone increases the thermal stability.…”
Section: Introductionmentioning
confidence: 99%